The factors contribute to depository in islamic savings account: a case study in Maybank Islamic Berhad Melaka / Kifah Afifi Mohamad Anuar and Zuhratul Nadhiera Zulkifli - Mohamad Anuar, Kifah Afifi; Zulkifli, Zuhratul Nadhiera (Faculty of Business and Management, 2013)
Nowadays, there is an increasing numbers of people who choose the Islamic savings account offered by Islamic Banks. As Maybank Islamic Berhad has been known as one of the banks offering Islamic financial products and services to the public, it had attracted our attention to investigate the factors contributing to the depository in Islamic savings account in Maybank Islamic Berhad. The objectives in this research are: 1) To investigate whether there is significant relationship between the attitude of the customers and their intention to choose Islamic savings account; 2) To determine if there is significant relationship behavioral control and customers’ intention to choose Islamic savings account; 3) To investigate whether there is positive relationship between size and reputation of the bank with customers’ intention to choose Islamic savings account; 4) To indicate the relationship between cost and benefits of choosing the Islamic Deposits and intention to choose Islamic savings account; and 5) To identify the most influential factor that contributes to the depository in Islamic savings account. This study has been conducted to 150 customers in Maybank Islamic Berhad Malacca Branch and the data collected were analyzed using the Statistical Package for Social Sciences (SPSS). The data analyzed to determine the relationship between independent variable; attitude, perceived behavioral control, size and reputation of the bank and cost and benefits, with the dependent variable which is the intention. The data analyzed to obtain results on Reliability Test, Correlation Test, and Regression Analysis. The results showed that all the independent variables have significant relationship with the dependent variable. The most influential factor that contributes to depository in Islamic savings account is the attitude of the customers.